Online purchasing behaviour among the younger generation / Cheong Su Ling and Susan Chin Tee Suan - Cheong, Su Ling; Chin, Susan Tee Suan (2012)
The purpose of this study is to examine the online purchasing behaviour of the younger generation. A total of 300 people took part in this survey. It was found that a majority from the online shoppers are from the urban areas and that they purchase goods online at least once a month. Security issues are still the main concern of online shoppers.